Who Cares About Social Image? - Dirk Engelmann; Jana Friedrichsen (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2018)
This paper experimentally investigates how concerns for social approval relate to intrinsic motivations to purchase ethically. Participants state their willingness-to-pay for both a fair trade and a conventional chocolate bar in private or publicly. A standard model of social image predicts that all participants increase their fair trade premium when facing an audience. We find that the premium is indeed higher in public than in private. This effect, however, is driven by participants who preferred a conventional chocolate bar over a fair trade one in a pre-lab choice. For those who chose the fair trade chocolate bar, public exposure does not change the fair trade premium. This is captured by a generalized model where intrinsic preferences and the concern for social approval are negatively correlated.
Keywords: C91; D12; 330; image concerns; ethical consumption; fair trade; social approval; experiments